Epidural analgesia for hyperbaric oxygen therapy in a patient with Nicolau Syndrome - Moreira, Joana Fonseca (2016)
Nicolau syndrome is a rare complication following intramuscular injection, leading to local ischemic necrosis. The authors present a case of a 3-year-old boy who was admitted with Nicolau syndrome after intramuscular penicillin injection and then proposed for hyperbaric oxygen therapy. On the 3rd day after admission an epidural catheter was inserted and a perfusion of ropivacaine was initiated. 24 hours after the epidural block the pain was under control and 48 hours after the block the patient was extubated. The hyperbaric oxygen therapy treatment was performed without any events. There are numerous treatments described for Nicolau syndrome, however, there is not a gold standard treatment established. Pain treatment with epidural analgesia seems a good option, particularly in pediatric patients, allowing a satisfactory adhesion to the other treatments. The authors also attested the security and efficacy of epidural catheters during hyperbaric oxygen therapy.